Exploring Intraovarian Platelet-Rich Plasma (PRP) Therapy: A New Hope for Polycystic Ovary Syndrome (PCOS) Patients - Aru Chaudhary; Akash More; Namrata Choudhary; Juhi Barai; Tejaswini Wadhe (Journal of Pharmacy and Bioallied Sciences)
This case study represents a couple experiencing primary infertility for 4 years, with the male suffering from hypertension and normozoospermic condition, whereas the female suffers from Polycystic Ovary Syndrome (PCOS), which results in low ovarian reserve. The couple underwent the two failed IUI (Intrauterine Insemination) procedures and then was advised to go for Intra-cytoplasmic sperm injection (ICSI). After the first unsuccessful cycle of ICSI, the female patient underwent intraovarian platelet-rich plasma (PRP) therapy to improve the ovarian reserve and enhance egg quality. The second cycle of ICSI following the PRP treatment helped to improve ovarian response with more mature oocytes retrieved. After another ovum pick-up was conducted in which more mature oocytes were retrieved and after multiple embryo transfer (ET) cycles, a positive pregnancy was achieved. The patient was asked to have regular checkups during pregnancy. This study results in the potential benefit of intraovarian PRP therapy in enhancing ovarian function and reserve.